The method of interpretation as discovery - Herth, Ákos (Acta Cultura et Paedagogicae, 2026)
The study explores the interpretative method as a means of discovery, focusing on Alfred North Whitehead's philosophy of language and experience. Whitehead's metaphysical framework suggests that all events in nature are expressions, where human language serves as a heightened phase of this expressive process. The research examines the role of propositions, consciousness, and the symbolic nature of language in shaping human thought. Additionally, it draws parallels with the phenomenology of Merleau-Ponty and highlights the transformative nature of interpretation. By framing philosophy as an experimental practice, the study argues that conceptual thinking is not merely about defining meaning but actively transforming experience.